Behavioral interviewing with couples - Stockton, Phil.; Gottman, John.; Behavioral Images, inc.; Research Press Company (Champaign, Ill. : Research Press, 1976)
Demonstrates one method for behaviorally interviewing couples during initial counseling. Shows an initial interview in which the behavior of the couple and the clinically experienced therapist are fully observable.
VHS format.
Cinematographer, Robert Young.
Gloria Dorson, William Kinzer, John Gottman.
Keywords: Marriage counseling